Analisis Proses Rekrutmen dan Kaderisasi Perempuan di Partai Gerakan Indonesia Raya Kabupaten Ponorogo: Analysis of recruitment and regeneration process of Gerakan Indonesia Raya Party DPC Ponorogo Regency - Wahyu Tristiana; Ekapti Wahjuni Dj; Dian Suluh Kusuma Dewi (JOURNAL OF GOVERNMENT SCIENCE, 2023)
This paper aims to see how the Recruitment and Cadreization Process of Women in the Great Indonesia Movement Party, Ponorogo Regency. This study uses a qualitative descriptive research design approach. The results of the study stated that the Gerindra Party DPC Ponorogo Regency uses an open recruitment procedure using selection where every citizen has the right to receive equal treatment and to participate in the political process by joining a political party, not only the party also judges from the experience of the organization, popularity and financial potential of cadre candidates who are prepared as legislative candidates. The process of recruiting political parties is the beginning of political parties, the purpose of which is to prepare recruited cadres who can compete with political cadres from other parties and have the ability to carry out their duties and obligations when elected in the political competition. the recruitment process includes the process of preparing human resources so that in the future they become leaders who can better build the roles and functions of the party and this regeneration is carried out in stages and systematically. Even in political party institutions, affirmative action is carried out by requiring political parties to include at least female representatives in 30% of the establishment as well as in management at the central level